Predictive factors of mortality in damage control surgery for abdominal trauma - LEONARDI,LUIZA (2022)
ABSTRACT Introduction: damage control surgery (DCS) is well recognized as a surgical strategy for patients sustaining severe abdominal trauma. Literature suggests the indications, operative times, therapeutic procedures, laboratory parameters and intraoperative findings have a direct bearing on the outcomes. Objective: to analyze the clinical profile of patients undergoing DCS and determine predictors of morbidity and mortality. Methods: a retrospective cohort study was conducted on all patients undergoing DCS following abdominal trauma from November 2015 and December 2021. Data on subjects’ demographics, baseline presentation, mechanism of injury, associated injuries, injury severity scores, laboratory parameters, operative details, postoperative complications, length of stay and mortality were assessed. A binary logistic regression analysis was performed to determine potential risk factors for mortality. Results: During the study period, 696 patients underwent trauma laparotomy. Of these, 8.9% (n=62) were DCS, with more than 80% due to penetrating mechanisms. Overall mortality was 59.6%. In the logistic regression stratified by survival, several variables were significantly associated with mortality, including hypotension, and altered mental status at admission, intraoperative cardiorespiratory arrest, need for resuscitative thoracotomy, metabolic acidosis, hyperlactatemia, coagulopathy, fibrinolysis, and severity of the trauma injury scores. Conclusion: DCS may be appropriate in critically injured patients; however, it remains associated with significant morbidity and high mortality, even at specialized trauma care centers. From pre and postoperative clinical and laboratory parameters, it was possible to predict the risk of death in the studied sample.